2017
DOI: 10.1080/19440049.2017.1326067
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tenax® films to demonstrate the migration of chemical contaminants from cardboard into dry food

Abstract: Contaminants in food packaging are a challenge of our time since the packaging material itself has been found to represent a source of food contamination through the migration of substances from it. Before first use, packaging materials destined for the packaging of dry foods can be evaluated by performing migration experiments with the simulant for dry foods, Tenax®. This simulant is commercially available as a powder that is more difficult to handle during the migration experiments. This paper reports the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Next, the samples were extracted and analyzed for various substances. Previous studies on paper and board often indicated the presence of bisphenols, phthalates, photoinitiators and mineral oil ( Biedermann and Grob, 2010 ; Vollmer et al, 2011 ; Fierens et al, 2012 ; Pérez-Palacios et al, 2012 ; Bradley et al, 2013 ; Suciu et al, 2013 ; Zurfluh et al, 2013 ; Pivnenko et al, 2016 ; Van Den Houwe et al, 2016 ; Vápenka et al, 2016 ; Vavrouš et al, 2016 ; Jurek and Leitner, 2017 ; Van Den Houwe et al, 2017 ). Therefore, these substances were targeted in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the samples were extracted and analyzed for various substances. Previous studies on paper and board often indicated the presence of bisphenols, phthalates, photoinitiators and mineral oil ( Biedermann and Grob, 2010 ; Vollmer et al, 2011 ; Fierens et al, 2012 ; Pérez-Palacios et al, 2012 ; Bradley et al, 2013 ; Suciu et al, 2013 ; Zurfluh et al, 2013 ; Pivnenko et al, 2016 ; Van Den Houwe et al, 2016 ; Vápenka et al, 2016 ; Vavrouš et al, 2016 ; Jurek and Leitner, 2017 ; Van Den Houwe et al, 2017 ). Therefore, these substances were targeted in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 10 years, paper and board FCM have been studied extensively. Many contaminants, such as phthalates ( Fierens et al, 2012 ; Pivnenko et al, 2016 ; Vápenka et al, 2016 ; Vavrouš et al, 2016 ; Van Den Houwe et al, 2017 ), printing inks ( Bradley et al, 2013 ; Van Den Houwe et al, 2016 ; Vápenka et al, 2016 ; Van Den Houwe et al, 2017 ), bisphenols ( Pérez-Palacios et al, 2012 ; Suciu et al, 2013 ; Jurek and Leitner, 2017 ) as well as mineral oil hydrocarbons (MOH) ( Biedermann and Grob, 2010 ; Dima et al, 2011 ; Vollmer et al, 2011 ; Zurfluh et al, 2013 ; Fengler et al, 2015 ; Pivnenko et al, 2016 ), were often reported in the literature as contaminants. Perez-Palacios et al showed the presence of bisphenol A (BPA) in recycled paper and board hamburger boxes, milk bricks, pizza boxes, and packaging ( Pérez-Palacios et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%